An assessment of Parkinson's disease medication treatment patterns in the Medicaid population. (2021) - Johnsrud, Michael; Richards, Kristin; Arcona, Steve; Sasané, Rahul; Leoni, Matthew
Highlights: There is a lack of published research assessing Parkinson's disease medication treatment patterns in Medicaid programs. Roughly half of Parkinson's disease patients in our study who initiated on levodopa or a dopamine agonist had a baseline depressive disorder. Adherence rates are suboptimal following initiation of either levodopa or a dopamine agonist for patients with PD in Medicaid programs. Adherence and persistence rates were better for patients initiating on levodopa. Abstract: Introduction: Most Parkinson's disease (PD) medication adherence studies have focused on patients with commercial or Medicare health insurance coverage. However, less is known regarding medication treatment patterns within the Medicaid population. Methods: This retrospective cohort study utilized 2011–2019 administrative healthcare claims from 7 state Medicaid programs. We compared newly diagnosed patients with PD started on either levodopa or a dopamine agonist (DA). Baseline comorbidities were compared. Outcomes were assessed during a 12-month post-index observation period, and included total medication days, proportion of days covered (PDC), adherence status, persistence to initiating PD medication, and time to non-persistence of initiating PD medication. Results: Our study sample of 805 Medicaid patients had an average age of 54.1 years, with 52.0% being female. Levodopa was the predominant PD medication at initiation (75.4%). Roughly half of patients had a baseline depressive disorder and nearly 40% had an anxiety disorder. Levodopa patients had a significantly higher PDC compared to DA patients (0.621 vs. 0.546, p = 0.007). An adjusted logistic regression model showed no significant difference in the number of adherent patients between the two groups (p = 0.058). An adjusted Cox proportional hazards model controlling for demographic and baseline variables showed a 26% lower risk of non-persistence for levodopa patients versus DA patients (HR 0.740, CI 0.597–0.917, p = 0.006). Conclusions: Adherence and persistence rates were suboptimal following initiation of either levodopa or DA medication for patients with PD in Medicaid programs, though rates were better for those initiated on levodopa.